Khảo sát ảnh hưởng của hàm lượng santopren đến tính chất của vật liệu polyme blend trên cơ sở cao su tự nhiên/polypropylen/santopren - Mỹ Hạnh, Lê Thị; Thanh Vân, Trần Thị (Vietnam Journal of Chemistry, 2014)
This paper presents the results relating to the influence of santopren (SAN) content to the properties of polymer blend based on natural rubber (NR) and polypropylen (PP) with the presence of peroxide initator. The properties of polymer blend are best when the content of SAN is 10%. The initial tensile strength is 19.27 MPa, after the accelerating weather test it remained above 86%. The thermal gravimetric analysis (TGA) showed that the polymer blend with 10%SAN was resistant up to 250oC. This polymer would be degraded more slowly than that of the polymer blend without SAN